EXPERIMENTAL INVESTIGATION OF STRENGTH AND WORKABILITY OF M20 GRADE FLY ASH BASED SCC (International Journal of Food and Nutritional Sciences, 2022)
Admixtures of minerals and chemicals are mostly used in concrete as a means of achieving full compaction, especially in cases of reinforcement congestion and a labor scarcity. Previous studies have emphasized that adding chemical and mineral admixtures to concrete gives it the desired characteristics when it's both fresh and hardened. The purpose of this research is to investigate the performance of self-compacting concrete with cement contents of 0%, 5%, 10%, 15%, and 20% fly ash. Five mixes of M20 grade self-compacting concrete were tested experimentally for both fresh and hardened qualities; the findings are compared with those of regular vibrated concrete. The following tests are taken into consideration for the study: the compressive strength, unit weight, compaction factor, and slump tests. The findings demonstrate that, while the water cement ratio is constant, adding more superplasticizer to self-compacting concrete improves its ability to self-compact while also somewhat lowering its unit weight. Additionally, the compressive strength is somewhat higher than with a typical concrete mix.